Development Of Performance Evaluation And Prediction Models In Logistics Service And Supply Networks Towards A Sustainable And Robust Supply Chain - Jomthanachai, Suriyan (2022)
The main objective of this research is to develop an optimization model for a novel network data envelopment analysis and machine learning algorithms. And to utilize the models as tools and metrics for evaluating and predicting supply chain performance.